Effects of the Probiotic Enterococcus faecium and Pathogenic Escherichia coli Strains in a Pig and Human Epithelial Intestinal Cell Model. (26th March 2015) - Lodemann, Ulrike; Strahlendorf, Julia; Schierack, Peter; Klingspor, Shanti; Aschenbach, Jörg R.; Martens, Holger
Abstract : The aim of this study has been to elucidate the effect of the probiotic Enterococcus faecium NCIMB 10415 on epithelial integrity in intestinal epithelial cells and whether pre- and coincubation with this strain can reproducibly prevent damage induced by enterotoxigenic (ETEC) and enteropathogenic Escherichia coli (EPEC). Porcine (IPEC-J2) and human (Caco-2) intestinal epithelial cells were incubated with bacterial strains and epithelial integrity was assessed by measuring transepithelial electrical resistance (TEER) and mannitol flux rates. E. faecium alone increased TEER of Caco-2 cells without affecting mannitol fluxes whereas the E. coli strains decreased TEER and concomitantly increased mannitol flux rates in both cell lines. Preincubation with E. faecium had no effect on the TEER decrease induced by E. coli in preliminary experiments. However, in a second set of experiments using a slightly different protocol, E. faecium ameliorated the TEER decrease induced by ETEC at 4 h in IPEC-J2 and at 2, 4, and 6 h in Caco-2 cells. We conclude that E. faecium positively affected epithelial integrity in monoinfected Caco-2 cells and could ameliorate the damage on TEER induced by an ETEC strain. Reproducibility of the results is, however, limited when experiments are performed with living bacteria over longer periods.